Gellan microgels produced in planar microfluidic devices. (September 2017) - Costa, Ana Letícia Rodrigues; Gomes, Andresa; Ushikubo, Fernanda Yumi; Cunha, Rosiane Lopes
Abstract: Microgels were obtained from the droplets gelation of a water-in-oil emulsion containing gellan in the aqueous phase. Gellan gum (0.6% w/w) and calcium acetate (0.5 and 2.0% w/w) as gelling agent were used to produce the microgels. The effect of the continuous phase flow rate and salt concentration on the particle size and size polydispersity of the gellan microgels was evaluated, as well as microchannels configuration for encapsulation of hydrophilic compounds in these particles using planar microfluidics devices. The microgels exhibited uniform and spherical shape. A highly monodisperse particle size distribution was observed showing coefficient of variation below 5% and average size ranging from 63 to 113 μm. Increasing salt concentration caused an increase of the mean particle diameter and a decrease of the size polydispersity. However at high salt concentration the continuous flow rate did not exert significant effect on the microgel size since average size ranged from 106 to 113 μm. A potential use of gellan microgels as encapsulating matrix of active compounds was evaluated by adding a hydrophilic dye, Rhodamine B, in the aqueous phase. Results showed good retention capacity of the dye and stability over time of storage, indicating that microgels obtained by microfluidics technique may be used for the encapsulation of hydrophilic compounds, including those sensitive to temperature and pressure, as well as in drug delivery. Highlights: Gellan microgels were formed from the disperse phase of a water-in-oil emulsion. Particle size distribution was highly monodisperse using planar microfluidic devices. Particle diameter increased and polidispersity decreased increasing salt concentration. Hydrophilic compound was successfully incorporated into gellan microgels.